Long-term osteogenic differentiation of human bone marrow stromal cells in simulated microgravity: novel proteins sighted - Montagna Giulia; Pani Giuseppe; Flinkman Dani; Cristofaro Francesco; Pascucci Barbara; Massimino Luca; Lamparelli Luigi A.; Fassina Lorenzo; James Peter; Coffey Eleanor; Rea Giuseppina; Visai Livia; et al. (SPRINGER BASEL AG, 2022)
Microgravity-induced bone loss is a major concern for space travelers. Ground-based microgravity simulators are crucial to study the effect of microgravity exposure on biological systems and to address the limitations posed by restricted access to real space. In this work, for the first time, we adopt a multidisciplinary approach to characterize the morphological, biochemical, and molecular changes underlying the response of human bone marrow stromal cells to long-term simulated microgravity exposure during osteogenic differentiation. Our results show that osteogenic differentiation is reduced while energy metabolism is promoted. We found novel proteins were dysregulated under simulated microgravity, including CSC1-like protein, involved in the mechanotransduction of pressure signals, and PTPN11, SLC44A1 and MME which are involved in osteoblast differentiation pathways and which may become the focus of future translational projects. The investigation of cell proteome highlighted how simulated microgravity affects a relatively low number of proteins compared to time and/or osteogenic factors and has allowed us to reconstruct a hypothetical pipeline for cell response to simulated microgravity. Further investigation focused on the application of nanomaterials may help to increase understanding of how to treat or minimize the effects of microgravity.